Políticas públicas municipais de saúde: fortalecendo a democracia em pequenos municípios brasileiros - Bizelli, Jose Luis [UNESP]; Bizelli, Sabrina Sinabucro Kanesiro [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP] (My University, 2014)
This article presents the endeavors of health municipal teams in building services that meet citizens’ demands, in a small municipality from a less developed area of the state of São Paulo. Beyond health services practice characterization and organization, our study assesses the challenges and advances in the implementation of public, health policies in Brazil. In this way it is possible to perceive how the family health strategy needs to overcome impasses in the service work processes, as well as more dynamic local and regional relations to provide comprehensive care to citizens. Health care exemplifies how, in democracy building, municipal action is indispensable to strengthen the effectiveness of public actions.

Este artigo apresenta o esforço das equipes municipais que atuam na área da saúde para a construção do atendimento das demandas cidadãs, em um pequeno município de uma área pouco desenvolvida do estado de São Paulo. A investigação analisa não só como as práticas do serviço de saúde se caracterizam e se organizam, mas quais são os desafios e os avanços presentes na implantação de políticas públicas de saúde, no Brasil. Assim, é possível perceber como a estratégia de saúde da família necessita de relações loco-regionais mais dinâmicas para dar atenção integral ao cidadão. Olhar sobre a saúde ilustra como, no caminho de construção da democracia, a ação municipal é imprescindível para fortalecer a resolutividade das ações públicas.
Municipal public health policies: strengthening local democracy in small municipalities
Keywords: Municipal management; Municipal public policies; Local health management; Brazilian small municipalities; Gestão municipal; Políticas públicas municipais; Gestão da saúde local; Pequenos municípios brasileiros